Prenatal diagnosis of congenital epulis by 2D/3D ultrasound and magnetic resonance - Frisova, Veronika; Prosova, Blanka; Mahdian, Nima; Kyncl, Martin; Vlk, Radovan; Rocek, Miloslav (Fetal diagnosis and therapy, 2013)
Congenital epulis is a rare benign oral cavity tumor that usually arises from the maxillary alveolar mucosa. It is also known as congenital gingival granular cell tumor. Prenatal diagnosis is uncommon and mostly confined to the third trimester. We report a case of congenital epulis, which was referred to our department at 35 weeks of gestation. Both images from our prenatal 2D/3D ultrasound (including Doppler technique) and magnetic resonance examination are presented. A baby girl weighing 2,800 g was delivered spontaneously at 36 weeks and 1 day. The newborn had to be intubated immediately after delivery. A simple excision of the mass was performed on the first day of neonatal life after clinical examination by our pediatric stomatologists confirmed the presence of a tumor resembling epulis. The correctness of this diagnosis was subsequently confirmed by histogenesis. Photographs from the operating room show the postnatal appearance of the tumor. The baby was discharged at the age of 19 days and has remained well at follow-up controls.
Keywords: Prenatal Diagnosis; Adult; zobrazování trojrozměrné; těhotenství; Infant, Newborn; výsledek terapie; ženské pohlaví; prenatální diagnóza; lidé; nádor z granulárních buněk; Granular Cell Tumor; Pregnancy; ultrasonografie prenatální; Pregnancy Trimester, Third; ultrasonografie dopplerovská barevná; třetí trimestr těhotenství; Ultrasonography, Prenatal; dospělí; Treatment Outcome; Humans; Magnetic Resonance Imaging; Ultrasonography, Doppler, Color; Imaging, Three-Dimensional; Female; nádory dásní; novorozenec; Gingival Neoplasms; magnetická rezonanční tomografie